Мировая история: [энциклопедия] / [В.А. Ведюшкин, Е.Н. Глазунова, О.В. Дмитриева и [др.] - Волкова А.В. (Детская энциклопедия " РОСМЭН", 2013)
Авт. указаны перед выпускными данными Экземпляры: ф.4 (20140701) / Инвентарный номер: 48716 / Цена: 86.00 / Авт.знак: М 64 / ГРНТИ: 03 / ББК: 63.3(0)